Between practice, policy and politics: Music therapy and the Dementia Strategy, 2009. (April 2017) - Spiro, Neta; Farrant, Camilla L; Pavlicevic, Mercédès
Does current music therapy practice address the goals encapsulated in the UK Department of Health document, Living well with dementia: a national dementia strategy (the Dementia Strategy) published in 2009? A survey elicited the views of clients, family members, music therapists, care home staff and care home managers, about this question by focusing on the relationship between music therapy and the 17 objectives outlined in the Dementia Strategy. The results showed that the objectives that are related to direct activity of the music therapists (such as care and understanding of the condition) were seen as most fulfilled by music therapy, while those regarding practicalities (such as living within the community) were seen as least fulfilled. Although the responses from the four groups of participants were similar, differences for some questions suggest that people's direct experience of music therapy influences their views. This study suggests that many aspects of the Dementia Strategy are already seen as being achieved. The findings suggest that developments of both music therapy practices and government strategies on dementia care may benefit from being mutually informed.